Generation of Cu–In alloy surfaces from CuInO2 as selective catalytic sites for CO2 electroreduction. Issue 37 (7th October 2015) - Jedidi, Abdesslem; Rasul, Shahid; Masih, Dilshad; Cavallo, Luigi; Takanabe, Kazuhiro
<x xml:space="preserve">Abstract</x> Selective electrocatalytic CO2 reduction was achieved using CuIn alloy synthesized from CuInO2.